ÁGUA E SAÚDE PÚBLICA: UMA PERSPECTIVA PÓS-COVID-19 - Vieira, José Manuel Pereira (Revista Eletrônica de Gestão e Tecnologias Ambientais, 2020)
Paper Position que aborda, na ótica de seu autor, a relação entre Água e Saúde Pública no contexto atual de pandemia da COVID-19 e as perspectivas para o seu “após”. ABSTRACT Paper Position that addresses, in the view of its author, the relationship between Water and Public Health in the current context of the COVID-19 pandemic and the prospects for its “after”.